Global pressure or national identity: strategic challenges for Russian business schools - Gerasimenko, Valentina; Molchanova, Olga (Serbian Journal of Management, 2017)
In the context of globalization of the business education market, Russian business schools face a complex managerial problem - how to preserve a business school’s identity. The parameters of demand for managerial education in Russia have become significantly more complicated, new global competitive pressure forces have arisen, compelling business schools to adjust and revise their strategies and comply with international standards of the global business education market. Normative pressure is one of the key reasons that encourage business schools to adapt successful overseas education models. However, the impact of market logic often covers normative appeals to adaptation, as reflected in copying and adoption of the US MBA model. Our research aims to show what the priorities of Russian business school MBA students are today in choosing a business school, as well as which of the competencies of graduates are most on demand in the Russian labour market. The research was conducted over a period of three years (from 2014 to 2016), 358 Lomonosov Moscow State University MBA program graduates who study in Russia and Kazakhstan participated in our questionnaires. The structure of qualities stated by our graduates raises serious challenges to the content and standards of MBA programs in the global context, especially considering the cultural code of the nation, manifested in the practice of doing business. Globalized and marketable specialized managerial knowledge is clearly a priority among graduates today. Greater attention is being devoted to new innovative models in the field of managerial education (edtech platforms, on-demand platforms, subscription model, freemium model, etc.). The development of innovative models by traditional business schools may cause tension between efficiency and innovation as well as conflicting managerial tasks. Among strategic priorities for Russian business schools under the influence of globalization we highlight: diversification of educational products and services; learning of a complex nature, which increasingly represents the integration of three types of activity: research + learning + consulting; reengineering of educational, organizational, administrative, and marketing processes performed at business schools. The forms of these directions implementation and their effectiveness in the context of the global education market should be the subject of further study.